Silicon-carbon negative electrode material and preparation method and application thereof
By preliminarily, delimiting, ball milling and carbonizing the silicon carbon material, a lithiation path is formed, and the volume expansion and stability of the silicon negative electrode material during the circulation process in lithium-ion batteries is solved, and a silicon carbon negative electrode material with high capacity and long cycle life is achieved.
Patent Information
- Application Number
- CN202411977293.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
AI Technical Summary
During the circulation of lithium-ion batteries, silicon negative electrode materials will lead to volume expansion, particle powdering, instability of solid electrolyte interfaces and loss of electrical contact, resulting in sharp attenuation of capacity and unsatisfactory cycle life.
By prelithizing the silicon carbon material and deliques it to form a lithiation path, thereby improving capacity and cycle stability in lithium-ion batteries. The specific method includes prelithium, chemical delithium, ball milling and carbonization treatment of the silicon carbon material to prepare the silicon carbon negative electrode material.
This method can significantly improve the capacity and cycle stability of silicon carbon anode material, extend the cycle life of the battery, and improve the overall performance of the battery.
Smart Images

Figure CN119864394A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon-carbon negative electrode, and in particular to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the introduction of the concepts of "carbon peak in 2030" and "carbon neutrality in 2060", the development of new energy vehicles is an important part of achieving this goal. For new energy vehicles, the most important thing is to improve their cruising range. As the core component of new energy vehicles, lithium-ion batteries need to have higher volume energy density and mass energy density due to volume and mass limitations. To achieve the high energy density of lithium-ion batteries, we mainly start from higher positive electrode specific capacity, higher negative electrode specific capacity and higher battery voltage. The specific capacity of the positive electrode material is relatively lower, and the performance improvement of lithium-ion batteries is not significant; and there is still a lot of room for exploring negative electrode materials with higher specific capacity to improve the energy density of lithium-ion batteries.
[0003] At present, the actual specific capacity of mature commercial graphite anodes is close to its theoretical specific capacity of 372 mAh g -1 Therefore, it is necessary to develop a new generation of negative electrode materials with higher specific capacity. The theoretical specific capacity of silicon can reach 3579~4200mAh g -1 (Li 3.75 Si~Li 4.4 Si), far exceeding the theoretical specific capacity of graphite negative electrode; and silicon has a lower operating voltage (0.1-0.5V vs Li / Li + ) and abundant resource reserves, suitable for large-scale production and application, and very suitable for the application needs of the next generation of high energy density lithium-ion batteries in the field of electric vehicles. However, in practical applications, silicon anode materials still face many challenges. For example, the silicon anode will undergo an alloying reaction with lithium during the cycle, causing a huge volume expansion (~300%). Such a huge volume change can lead to problems such as particle pulverization, solid electrolyte interface (SEI) instability, and electrical contact loss, resulting in a sharp decline in capacity and unsatisfactory cycle life. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0004] The purpose of the present invention is to provide a silicon-carbon negative electrode material and a preparation method and application thereof. By pre-lithiation and then delithiation of the silicon-carbon material, a lithiation path can be formed in the silicon-carbon material, so that after being applied to a lithium-ion battery, the capacity and cycle stability can be improved.
[0005] In a first aspect, the present invention provides a method for preparing a silicon-carbon negative electrode material, comprising: pre-lithiation of the silicon-carbon material to obtain a pre-lithiation material; chemically delithiation of the pre-lithiation material to obtain a delithiation material; and ball milling and carbonizing the delithiation material to obtain a silicon-carbon negative electrode material.
[0006] Optionally, when the silicon-carbon material is subjected to pre-lithiation to obtain the pre-lithiation material, the method includes: stirring and mixing the silicon-carbon material in a pre-lithiation solution, and then separating and drying to obtain the pre-lithiation material.
[0007] Optionally, the lithium solute in the pre-lithium solution includes one of 4,4'-dimethylbiphenyl lithium complex, n-butyl lithium, and 4-methylbiphenyl lithium complex.
[0008] Optionally, the solvent in the pre-lithium solution includes one of ethylene glycol dimethyl ether, cyclohexane, and 2-methyltetrahydrofuran.
[0009] Optionally, the molar concentration of lithium in the pre-lithium solution is 3 mol / L-4 mol / L.
[0010] Optionally, the silicon-carbon material is stirred and mixed in the pre-lithium solution for 0.5 h to 24 h.
[0011] Optionally, the silicon-carbon material is stirred and mixed in the pre-lithium solution at a rotation speed of 100 rpm-300 rpm.
[0012] Optionally, the silicon-carbon material is stirred and mixed in a pre-lithium solution at 10° C.-50° C.
[0013] Optionally, chemically delithiating the pre-lithium material to obtain the delithiated material comprises: delithiating the pre-lithium material in a delithiated solution through a chemical reaction, and then separating and drying to obtain the delithiated material.
[0014] Optionally, the delithiation solution comprises a phosphoric acid solution with a concentration of 0.001 mol / L-0.05 mol / L.
[0015] Optionally, the pre-lithium material is reacted in the delithiation solution for 3h-8h.
[0016] Optionally, the pre-lithium material is allowed to stand in the delithiation solution to react.
[0017] Optionally, after the pre-lithium material is delithiated by chemical reaction in a delithiation solution, the delithiation solution and deionized water are used to rinse alternately.
[0018] Optionally, the method for preparing the silicon-carbon material comprises: ball-milling, mixing, separating and drying a micron silicon material and a conductive carbon material in a liquid environment containing a dispersant to obtain the silicon-carbon material.
[0019] Optionally, the particle size of the micron silicon material is 0.5 μm-100 μm.
[0020] Optionally, the micron silicon material includes one of micron silicon particles, micron porous silicon, and micron silicon oxide particles.
[0021] Optionally, the conductive carbon material includes one of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanowires, carbon nanobelts, and carbon nanofibers.
[0022] Optionally, the dispersant includes one of polyvinyl pyrrolidone, polyvinyl alcohol, silane coupling agent, polyacrylic acid, carboxymethyl cellulose salt, ethyl cellulose, hydroxypropyl cellulose and chitosan.
[0023] In a second aspect, the present invention also provides a silicon-carbon negative electrode material prepared by any of the above optional preparation methods.
[0024] In a third aspect, the present invention further provides an application of a silicon-carbon negative electrode material prepared by any of the above optional preparation methods, wherein the application includes a lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A flowchart of a method for preparing a silicon-carbon negative electrode material provided by the present invention;
[0026] Figure 2 is a SEM image of the micron silicon particles prepared in Preparation Example 1 of the present invention;
[0027] Figure 3 This is a SEM image of the silicon-carbon negative electrode material prepared in Example 1 of the present invention;
[0028] Figure 4 XRD diagrams of the silicon-carbon negative electrode materials prepared in Examples 1 to 3 of the present invention;
[0029] Figure 5 This is a cycle performance curve diagram of the silicon-carbon negative electrode material prepared in Example 2 of the present invention after being assembled into a button battery;
[0030] Figure 6 This is a rate performance curve diagram of the silicon-carbon negative electrode material prepared in Example 2 of the present invention after being assembled into a button battery;
[0031] Figure 7 This is a cyclic voltammetric performance diagram of the silicon-carbon negative electrode material prepared in Example 2 of the present invention after being assembled into a button cell;
[0032] Figure 8 The cycle performance curves of the silicon-carbon negative electrode materials in Examples 1 to 3 and Preparation Example 2 of the present invention after being assembled into button batteries;
[0033] Fig. 9 The rate performance curves of the silicon-carbon negative electrode materials in Examples 1 to 3 and Preparation Example 2 of the present invention after being assembled into button batteries;
[0034] Fig.10These are AC impedance test diagrams of the silicon-carbon negative electrode materials in Examples 1 to 3 and Preparation Example 2 of the present invention after being assembled into button batteries. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0036] See also Figure 1 The present invention provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0037] S1. Pre-lithiation the silicon-carbon material to obtain a pre-lithiation material;
[0038] S2, chemically delithiating the pre-lithium material to obtain a delithiated material;
[0039] S3. The delithiation material is ball-milled and then carbonized to obtain a silicon-carbon negative electrode material.
[0040] In fact, when executing step S1, it includes: stirring and mixing the silicon-carbon material in the pre-lithium solution, separating and drying to obtain the pre-lithium material. Specifically, the lithium solute in the pre-lithium solution used includes one of 4,4'-dimethylbiphenyl lithium complex, n-butyl lithium, and 4-methylbiphenyl lithium complex, and the solvent in the pre-lithium solution includes one of ethylene glycol dimethyl ether, cyclohexane, and 2-methyltetrahydrofuran. In addition, the molar concentration of lithium in the pre-lithium solution is 3mol / L-4mol / L.
[0041] Specifically, in step S1, the silicon-carbon material is stirred and mixed in the pre-lithium solution at a speed of 100 rpm-300 rpm for 0.5 h-24 h to promote uniform pre-lithium insertion of the silicon-carbon material. In addition, the silicon-carbon material can be stirred and mixed in the pre-lithium solution at 10° C.-50° C. In fact, from the perspective of reaction convenience and environmental protection, the silicon-carbon material can be added to the pre-lithium solution at room temperature for stirring and mixing.
[0042] In some embodiments, when executing step S2, it includes: removing lithium from the pre-lithium material by chemical reaction in a de-lithiation solution, and then separating and drying to obtain the de-lithiation material. In fact, the de-lithiation solution includes a phosphoric acid solution with a concentration of 0.001 mol / L-0.05 mol / L, and the pre-lithium material is mixed in the phosphoric acid solution and reacted to generate lithium phosphate precipitate, thereby de-lithiation the pre-lithium material.
[0043] In some embodiments, when performing step S2, the pre-lithium material is allowed to stand in the delithiation solution for 3h-8h to remove the lithium element in the pre-lithium material. In addition, after the delithiation is completed by the standing reaction, the delithiation solution and deionized water are used to alternately rinse it to remove the lithium phosphate precipitate adhering to the surface of the delithiation material. In fact, after washing, it can be dried to constant weight in an environment of 50°C-80°C to obtain a pure delithiation material.
[0044] In some embodiments, when the de-lithium material is ball-milled in step S3, the de-lithium material is mixed with a dispersant and a dispersing solvent and then subjected to high-energy ball milling in a ball milling device, and then dried and sieved after the ball milling is completed. In practice, the dispersant used includes one of polyvinyl pyrrolidone, polyvinyl alcohol, a silane coupling agent, polyacrylic acid, carboxymethyl cellulose salt, ethyl cellulose, hydroxypropyl cellulose and chitosan, and the dispersing solvent used includes one of deionized water, N-methyl pyrrolidone and ethanol.
[0045] In some embodiments, when the delithiation material is carbonized after ball milling in step S3, high temperature calcination is performed under a protective atmosphere at 600°C-900°C. In fact, by carbonizing the delithiation material after ball milling, the dispersant mixed therein can be carbonized, thereby improving the purity of the silicon-carbon material and improving the structural stability of the silicon-carbon material. Specifically, the protective atmosphere includes one of argon, nitrogen, helium, and neon.
[0046] In some embodiments, when the delithiation material after ball milling is carbonized in step S3, the delithiation material after ball milling can be placed in a furnace of a tubular furnace, and after the gas in the tubular furnace is replaced with a protective atmosphere, the temperature in the tubular furnace is increased to 600°C-900°C at a rate of 2°C / min-10°C / min for heat preservation and calcination.
[0047] Specifically, the preparation method of the silicon-carbon material used in step S1 is as follows: the micron silicon material and the conductive carbon material are ball-milled, mixed, separated and dried in a liquid environment containing a dispersant to obtain the silicon-carbon material. In fact, by ball-milling and blending the micron silicon material and the conductive carbon material, the mixing uniformity of the silicon material and the carbon material can be effectively improved, while the particle size consistency and surface defects of the silicon-carbon material can be improved, which is beneficial to the subsequent pre-lithiation and de-lithiation of the silicon-carbon material.
[0048] In some embodiments, the particle size of the micron silicon material used is 0.5 μm-100 μm. Specifically, the micron silicon material includes one of micron silicon particles, micron porous silicon, and micron silicon oxide particles, and the conductive carbon material used includes one of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanowires, carbon nanobelts, and carbon nanofibers.
[0049] In fact, when preparing silicon-carbon materials, ball milling is performed in a liquid environment in which a dispersant is dissolved, so that the dispersant can be used to improve the uniformity of dispersion of micron silicon materials and conductive carbon materials, thereby facilitating the formation of uniform silicon-carbon materials during ball milling. Specifically, the dispersant used includes one of polyvinyl pyrrolidone, polyvinyl alcohol, silane coupling agent, polyacrylic acid, carboxymethyl cellulose salt, ethyl cellulose, hydroxypropyl cellulose and chitosan, and the liquid environment used includes one of deionized water, N-methyl pyrrolidone and ethanol.
[0050] Preparation Example 1
[0051] Preparation Example 1 provides a method for preparing micron silicon powder, comprising: adding 10 g of micron silicon particles into a ball mill, and adding 50 zirconia ball milling beads with a diameter of 2 mm and 25 zirconia ball milling beads with a diameter of 5 mm, and then adding 50 mL of deionized water, mixing and transferring to a planetary ball mill for high-energy ball milling dispersion, setting the ball mill speed to 250 rpm, the ball milling direction to alternate forward and reverse directions with an alternating time interval of 30 minutes, standing for 5 minutes during the alternation, and ball milling for a total of 2 hours; after the ball milling is completed, transferring to a 50°C forced air drying oven and drying to constant weight to obtain micron silicon powder.
[0052] Preparation Example 2
[0053] This Preparation Example 2 provides a preparation method for a silicon-carbon material, comprising: adding 3 g of micron silicon powder (Preparation Example 1), 1.125 g of carbon nanotubes (CNT, purchased from Clewin Nano Carbon Materials Co., Ltd.), and 0.9 g of polyvinyl alcohol (PVA, purchased from McLean) into a ball mill, and adding 50 zirconium oxide ball milling beads with a diameter of 2 mm and 25 zirconium oxide ball milling beads with a diameter of 5 mm, and then adding 25 mL of deionized water, mixing, and transferring to a planetary ball mill for high-energy ball milling dispersion, setting the ball mill speed to 250 rpm, the ball milling direction to alternate forward and reverse directions with an alternating time interval of 30 min, standing for 5 min during the alternation, and ball milling for a total of 2 h; after the ball milling is completed, transferring to a 50°C forced air drying oven and drying to constant weight, grinding in an agate mortar and passing through a 60-mesh sieve, collecting the sieved powder to obtain a silicon-carbon material (Si@C).
[0054] Example 1
[0055] This embodiment 1 provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:
[0056] S1. Add 0.6637 g of silicon-carbon material (Preparation Example 2) into a 3.306 mol / L 4,4'-dimethylbiphenyl lithium solution, stir at room temperature at a speed of 250 rpm for 6 h, and separate by suction to obtain a pre-lithium material;
[0057] S2, adding the pre-lithium material into 150mL of a dilute phosphoric acid solution with a concentration of 0.025mol / L, standing at room temperature for 6h, filtering and separating, and washing three times with a dilute phosphoric acid solution and deionized water alternately, and then transferring to a 50°C air drying oven and drying to constant weight to obtain a de-lithium material;
[0058] S3. The delithiation material was mixed with 25 ml of water and 5 ml of dispersant and then put into a spherical ink tank. 50 zirconium oxide ball milling beads with a diameter of 2 mm and 25 zirconium oxide ball milling beads with a diameter of 5 mm were added. The mixture was transferred to a planetary ball mill for high-energy ball milling dispersion. The ball milling speed was set to 250 rpm, and the ball milling direction was alternately forward and reversed with an alternating time interval of 30 min. The mixture was allowed to stand for 5 min during the alternation and the ball milling was carried out for a total of 2 h. After the ball milling, the mixture was transferred to a tubular furnace. In an argon atmosphere, the temperature was increased to 800 °C at a rate of 5 °C / min and then carbonized for 3 h. After cooling to room temperature with the furnace, the mixture was ground with an agate mortar and passed through a 500-mesh sieve to obtain a silicon-carbon negative electrode material (Si@C-6h).
[0059] Example 2
[0060] This embodiment 2 provides a method for preparing a silicon-carbon negative electrode material, which is different from the embodiment 1 in that in step S1, after stirring for 12 hours, the pre-lithium material is separated by filtration; in step S3, the silicon-carbon negative electrode material (Si@C-12h) is prepared.
[0061] Example 3
[0062] This embodiment 3 provides a method for preparing a silicon-carbon negative electrode material, which is different from the embodiment 1 in that in step S1, after stirring for 24 hours, the pre-lithium material is separated by filtration; in step S3, the silicon-carbon negative electrode material (Si@C-24h) is prepared.
[0063] Performance Testing
[0064] The micron silicon powder prepared in Preparation Example 1 and the silicon-carbon negative electrode material prepared in Example 1 were characterized by scanning electron microscopy using a GeminiSEM300 instrument from ZEISS, UK, at an operating voltage of 5kv-15kv. The results are as follows: Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the micron silicon particles are in the form of large bulk particles, while the silicon material in the silicon-carbon negative electrode material obtained after treatment has a smaller particle size and can be evenly distributed.
[0065] The silicon-carbon negative electrode materials prepared in Examples 1 to 3 were analyzed by X-ray diffraction using a German Bruker D8 Advance X-ray diffractometer and a copper target as the target material at 10°<2θ<90°, a tube voltage of 40 kV, a tube current of 40 mA, and a scanning rate of 10° / min. Figure 4 As shown. Figure 4 It can be seen that compared with the silicon standard card (JCPDS No.27-1402), the silicon-carbon negative electrode materials with different pre-lithium embedding times have characteristic peaks of silicon at diffraction angles 2θ of 28.4°, 47.3°, 56.1°, 69.1°, 76.4° and 88.0°. These characteristic peaks correspond to the (111), (220), (311), (400), (331) and (422) crystal planes of cubic crystalline silicon, which shows that the diffraction peaks of the silicon-carbon negative electrode with different pre-lithium embedding times are basically consistent with those of crystalline silicon, and will not change the crystal structure of micron silicon.
[0066] The silicon-carbon negative electrode material prepared in Example 2 was mixed with carbon black and carboxymethyl cellulose at a mass ratio of 6:2:2 for 12 hours to prepare a conductive slurry, and the conductive slurry was coated and dried on a copper foil to prepare a silicon-carbon negative electrode plate, and the silicon-carbon negative electrode plate was assembled with a lithium hexafluorophosphate electrolyte, a Celgard 2400 polymer separator and a lithium sheet into a button battery. The battery test system (CT-4008T) of Nanjing Mojies Energy Technology was used to test the following items at 0.005V-2.000V:
[0067] Cycle performance: After activation at a current density of 0.02C (1C = 4200mA / g) for the first cycle, the charge and discharge performance test was performed at a current density of 0.1C for 100 cycles. The results are as follows Figure 5 As shown;
[0068] Rate performance: After being activated for two cycles at a current density of 0.05C (1C = 4200mA / g), the battery was cycled for five cycles at 0.05C and the charge-discharge curve was recorded. Then, the battery was cycled for five cycles at 0.1C and the charge-discharge curve was recorded. Then, the battery was cycled for five cycles at 0.2C and the charge-discharge curve was recorded. Then, the battery was cycled for five cycles at 0.5C and the charge-discharge curve was recorded. Then, the battery was cycled for five cycles at 1.0C and the charge-discharge curve was recorded. The results are as follows: Figure 6 shown.
[0069] The button cell corresponding to Example 2 was subjected to cyclic voltammetry test at a scan voltage of 0.005 V to 2.000 V and a scan rate of 0.1 mV / s using a Shanghai Chenhua electrochemical workstation (CHI660E). The results are shown in FIG. Figure 7 As shown. Figure 7 It can be seen that during the first cycle of charging, two strong oxidation peaks appear near 0.38V and 0.53V. At this time, the lithium-silicon alloy de-lithiates and undergoes a dealloying reaction, and the lithium-silicon alloy is converted into amorphous silicon. When the next round of discharge is around 0.13V, the corresponding reaction is an alloying reaction in which amorphous silicon is embedded with lithium to form a lithium-silicon alloy.
[0070] The silicon-carbon negative electrode materials prepared in Examples 1 to 3 and Preparation Example 2 were mixed with carbon black and carboxymethyl cellulose at a mass ratio of 6:2:2 for 12 hours to prepare a conductive slurry, and the conductive slurry was coated and dried on a copper foil to prepare a silicon-carbon negative electrode sheet. The silicon-carbon negative electrode sheet was assembled with a lithium hexafluorophosphate electrolyte, a Celgard 2400 polymer separator and a lithium sheet into a button battery. The battery test system (CT-4008T) of Nanjing Mojies Energy Technology was used to test the following items at 0.005V-2.000V:
[0071] Cycle performance: After activation at a current density of 0.02C (1C = 4200mA / g) for the first cycle, the charge and discharge performance test was performed at a current density of 0.1C for 100 cycles. The results are as follows Figure 8 As shown;
[0072] Rate performance: After being activated for two cycles at a current density of 0.05C (1C = 4200mA / g), the battery was cycled for five cycles at 0.05C and the charge-discharge curve was recorded. Then, the battery was cycled for five cycles at 0.1C and the charge-discharge curve was recorded. Then, the battery was cycled for five cycles at 0.2C and the charge-discharge curve was recorded. Then, the battery was cycled for five cycles at 0.5C and the charge-discharge curve was recorded. Finally, the battery was cycled for five cycles at 1.0C and the charge-discharge curve was recorded. The results are shown in the figure. Fig. 9 shown.
[0073] from Figure 8 It can be seen that the cycle performance of the silicon-carbon negative electrode material prepared in Preparation Example 2 is the worst, with only 264.4 mAh / g after 100 cycles, while the silicon-carbon negative electrode materials in Examples 1 to 3 have a specific capacity of 525.1 mAh / g, 912.4 mAh / g, and 736.6 mAh / g, respectively, after 100 cycles of long cycling, and have a higher capacity retention rate.
[0074] from Fig. 9 It can be seen that the charge and discharge capacities of the silicon-carbon negative electrode materials in Examples 1 to 3 and Preparation Example 2 at a low current density of 0.05C are not much different, but when cycled at a higher current density, the silicon-carbon negative electrode in Examples 1 to 3 that is de-lithiated after lithium insertion has a higher reversible capacity and capacity retention rate.
[0075] The button cells corresponding to Examples 1 to 3 and Preparation Example 2 were tested for AC impedance using a Shanghai Chenhua electrochemical workstation (CHI660E) at a frequency range of 100kHz-0.01Hz and an AC signal amplitude of 5mV. The results are shown in Table 1. Fig.10 As shown. Fig.10 It can be seen that the silicon-carbon negative electrode materials in Examples 1 and 2 have smaller charge transfer resistance than that in Preparation Example 2.
[0076] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: include: Pre-lithiation the silicon-carbon material to obtain a pre-lithiation material; Chemically delithiating the pre-lithium material to obtain a delithiated material; The delithiation material is ball-milled and then carbonized to obtain a silicon-carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: When the silicon-carbon material is subjected to pre-lithiation to obtain the pre-lithiation material, the method comprises: stirring and mixing the silicon-carbon material in a pre-lithiation solution, and then separating and drying to obtain the pre-lithiation material.
3. The preparation method according to claim 2, characterized in that: The lithium solute in the pre-lithium solution includes one of 4,4'-dimethylbiphenyl lithium complex, n-butyl lithium, and 4-methylbiphenyl lithium complex; and / or, the solvent in the pre-lithium solution includes one of ethylene glycol dimethyl ether, cyclohexane, and 2-methyltetrahydrofuran; and / or, the molar concentration of lithium in the pre-lithium solution is 3mol / L-4mol / L.
4. The preparation method according to claim 2, characterized in that: The silicon-carbon material is stirred and mixed in the pre-lithium solution for 0.5h-24h; and / or, the silicon-carbon material is stirred and mixed in the pre-lithium solution at a rotation speed of 100rpm-300rpm; and / or, the silicon-carbon material is stirred and mixed in the pre-lithium solution at 10°C-50°C.
5. The preparation method according to claim 1, characterized in that: When the pre-lithium material is subjected to chemical delithiation to obtain the delithiation material, the method comprises: delithiation of the pre-lithium material by chemical reaction in a delithiation solution, and then separation and drying to obtain the delithiation material.
6. The preparation method according to claim 5, characterized in that: The delithiation solution comprises a phosphoric acid solution with a concentration of 0.001 mol / L-0.05 mol / L; and / or, the pre-lithiation material is reacted in the delithiation solution for 3h-8h; and / or, the pre-lithiation material is allowed to stand in the delithiation solution for reaction; and / or, after the pre-lithiation material is delithiated by chemical reaction in the delithiation solution, the delithiation solution and deionized water are used to rinse alternately.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The method for preparing the silicon-carbon material comprises: ball-milling, mixing, separating and drying a micron silicon material and a conductive carbon material in a liquid environment containing a dispersant to obtain the silicon-carbon material.
8. The preparation method according to claim 7, characterized in that: The particle size of the micron silicon material is 0.5μm-100μm; and / or, the micron silicon material includes one of micron silicon particles, micron porous silicon, and micron silicon oxide particles; and / or, the conductive carbon material includes one of single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanowires, carbon nanobelts, and carbon nanofibers; and / or, the dispersant includes one of polyvinyl pyrrolidone, polyvinyl alcohol, silane coupling agent, polyacrylic acid, carboxymethyl cellulose salt, ethyl cellulose, hydroxypropyl cellulose, and chitosan.
9. A silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The applications include lithium-ion batteries.
Citation Information
Patent Citations
Modified silicon-carbon negative electrode material and preparation method and application thereof
CN112652757A
Preparation and application of in-situ polymerization coated modified silicon-based negative electrode material
CN113270586A
Porous silicon material and preparation method and application thereof
CN116282030A
Lithium ion battery silicon-carbon negative electrode material and preparation method thereof
CN118800893A
Delithiation solution and method for formation of anode active material or anode using same
US20230178709A1
Cited By
Lithium-intercalated silicon carbon material, preparation method thereof and application of lithium-intercalated silicon carbon material in lithium ion battery
CN120767318A
Silicon-carbon negative electrode material and preparation method thereof
CN120784323A